Combined modulation of tumor metabolism by metformin and diclofenac in glioma - Gerthofer, Valeria; Kreutz, Marina; Renner, Kathrin; Jachnik, Birgit; Dettmer, Katja; Oefner, Peter; Riemenschneider, Markus J.; Proescholdt, Martin; Vollmann-Zwerenz, Arabel; Hau, Peter; Seliger, Corinna (International Journal of Molecular Sciences, 2018)
Glioblastoma remains a fatal diagnosis. Previous research has shown that metformin, which is an inhibitor of complex I of the respiratory chain, may inhibit some brain tumor initiating cells (BTICs), albeit at dosages that are too high for clinical use. Here, we explored whether a combined treatment of metformin and diclofenac, which is a non-steroidal anti-inflammatory drug (NSAID) shown to inhibit glycolysis by interfering with lactate efflux, may lead to additive or even synergistic effects on BTICs (BTIC-8,-11,-13 and-18) and tumor cell lines (TCs, U87, and HTZ349). Therefore, we investigated the functional effects, including proliferation and migration, metabolic effects including oxygen consumption and extracellular lactate levels, and effects on the protein level, including signaling pathways. Functional investigation revealed synergistic anti-migratory and anti-proliferative effects of the combined treatment with metformin and diclofenac on BTICs and TCs. Signaling pathways did not sufficiently explain synergistic effects. However, we observed that metformin inhibited cellular oxygen consumption and increased extracellular lactate levels, indicating glycolytic rescue mechanisms. Combined treatment inhibited metformin-induced lactate increase. The combination of metformin and diclofenac may represent a promising new strategy in the treatment of glioblastoma. Combined treatment may reduce the effective doses of the single agents and prevent metabolic rescue mechanisms. Further studies are needed in order to determine possible side effects in humans.
CRIS-Team Scopus Importer:2023-03-23
Keywords: BTICs; Diclofenac; Glioma; Lactate; Metformin